Impact of mechanical pre-alloying on the densification and microstructure of Mo–10 %Nb sintered billets - Huacheng Du; Pengju Wang; Xiaochao Wu; Qingkui Li; Kaijun Yang; Longzhen Zhang; Ning Luo; JiaQiang Yang; Chengduo Wang; Jilin He (Journal of Materials Research and Technology)
Mo–10 %Nb alloy targets are extensively employed in the integrated circuit industry due to their superior corrosion resistance, thermal stability, and adhesion. However, fabricating Mo–10 %Nb alloy targets that exhibit both high density and uniformity presents substantial challenges. Previously, we synthesised and characterised Mo–10 %Nb alloy powder to enhance the performance of Mo–10 %Nb sputtering targets. This study employed a non-isothermal vacuum sintering method to sinter Mo–10 %Nb alloy powder, aiming to explore the densification process, the mechanisms of grain growth, element distribution, and the capacity for plastic deformation at high temperatures. Our findings indicate that during the later stages of sintering, pores within the alloy powder-sintered compact predominantly localize at grain boundaries. The primary mechanism for grain growth involves diffusion along these boundaries, with an activation energy for grain growth measured at 684.37 kJ mol−1. Moreover, subsequent to processing, the density of the sintered compact increased from 88.01 % to 93.26 %, while the average grain size reduced from 21.47 μm to 4.60 μm, significantly enhancing both compositional uniformity and microstructural homogeneity. Additionally, pre-alloying significantly enhanced the plastic deformation capability of the Mo–10 %Nb sintered compact at 1200 °C. This study demonstrates that Mo–10 %Nb alloy powder significantly improves the quality and the application value of Mo–10 %Nb targets in flat-panel display industry.